Student Teachers` Attitudes toward Using Literature as a Means of Language Teaching in a Multicultural Context - Alzaanin, Samar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Literature is an integral component of any language class as it represents the culture of the target language where students will have more exposure and that what lead to a better communicative competence which is the ultimate goal of language teaching. Thus, it was worth considering what do future teachers think about using literature as a means of language teaching in language classes. The current study is an attempt to investigate what do student teachers of ELT undergraduate program think about using literature in language classes especially in a context with students from different cultures and backgrounds as the case is in the university where this study was conducted. The study explored the student teachers` attitudes toward using literature from two different aspects; as learners enrolled in ELT program, and teachers in the near future willing to use literature in their language classes. According to the findings of the study, it was suggested that as a result for the misuse or the inappropriate selection of literary text in language classes, learners may be drifted behind some misconceptions, stereotypes, or cultural clashes as they are experiencing new culture. Thus, the study explored, as well, what consideration participants are going to keep in mind while choosing a literary text for language classes? The results of the study showed positive attitudes toward using literature as a means of language teaching and the participants are willing to use it in their literature classes as they believe that literature is a rich source of cultural authentic exposure. The results also suggested that there is no difference in the way of choosing literary text for a class of students from one culture or for a multicultural class. The consideration has only to do with students` level of proficiency and their own backgrounds. The very important and highlighted result of the study was the participants` belief about literature as it is a universal language that can be used anytime and anywhere and all people whatever their culture is can understand it.

ÖZ: Edebiyat, öğrencilerin daha fazla maruz kalacağı hedef dilin kültürünü temsil ettiği ve dil öğretiminin nihai amacı olan daha iyi bir iletişimsel yetkinliğe yol açan şeyin, herhangi bir dil sınıfının ayrılmaz bir bileşenidir. Bu nedenle, gelecekteki öğretmenlerin, edebiyatı dil derslerinde bir dil öğretimi aracı olarak kullanmaya ilişkin düşünceleri dikkate değerdi. Bu çalışma, ELT lisans programının öğrenci öğretmenlerinin, bu çalışmanın yapıldığı üniversitede olduğu gibi, özellikle farklı kültür ve geçmişlerden gelen öğrencilerle bir bağlamda dil derslerinde literatür kullanımı hakkında ne düşündüğünü araştırmak için bir girişimdir. Çalışma, öğretmen adaylarının edebiyatı iki farklı yönden kullanmaya yönelik tutumlarını incelemiştir; ELT programına kayıtlı öğrenenler ve yakın gelecekte öğretmenler edebiyatı kendi dil derslerinde kullanmaya istekli. Araştırmanın bulgularına göre, dil derslerinde edebi metnin yanlış kullanılması ya da yanlış seçilmesi sonucu, öğrencilerin yeni kültür yaşadıkları için bazı yanlış anlamalar, basmakalıp ya da kültürel çatışmaların arkasına sürüklenebileceği önerildi. Bu nedenle, araştırmada, katılımcıların dil dersleri için edebi bir metin seçerken akıllarında nelere dikkat etmeleri gerektiği araştırıldı. Çalışmanın sonuçları, edebiyatı dil öğretimi aracı olarak kullanmaya yönelik olumlu tutum sergilemiştir ve katılımcılar, literatürün zengin bir otantik maruz kalma kaynağı olduğuna inandıkları için, edebiyat derslerinde kullanmaya isteklidirler. Sonuçlar ayrıca, bir kültürden gelen bir öğrenci sınıfı için veya çok kültürlü bir sınıf için edebi metin seçme yolunda hiçbir fark olmadığını göstermiştir. Düşüncenin yalnızca öğrencilerin yeterlilik düzeyi ve kendi geçmişleriyle ilgisi var.
Master of Arts in English Language Teaching (ELT). Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Education, Dept. of Foreign Language Education, 2019. Supervisor: Assist. Prof. Dr. İlkay Gilanlıoğlu.
Keywords: English Language Teaching (ELT) Department; English Language--Study and Teaching; Literature; Attitudes; Student teachers; Authentic materials; Multicultural context